Conserved cis- and trans-acting determinants for replication initiation and regulation of replication fork movement in tetrahymenid species. - Yue, M (1998)
The rDNA minichromosomes of Tetrahymena thermophila and Tetrahymena pyriformis share a high degree of sequence similarity and structural organization. The T.thermophila 5' non-transcribed spacer (5' NTS) is sufficient for replication and contains three repeated sequence elements that are conserved in T.pyriformis , including type I elements, the only known determinant for replication control. To assess the role of conserved sequences in replication control, structural and functional studies were performed on T.pyriformis rDNA. Similar to T.thermophila , replication initiates exclusively in the 5' NTS, localizing to a 900 bp segment. Elongating replication forks arrest transiently at one site which bears strong similarity to a tripartite sequence element present at fork arrest sites in T.thermophila rDNA. An in vitro type I element binding activity indistinguishable from the T.thermophila protein, ssA-TIBF, was detected in T.pyriformis extracts. The respective TIBF proteins bind with comparable affinity to type I elements from both species, suggesting that in vivo recognition could cross species boundaries. Despite these similarities, the T.pyriformis 5' NTS failed to support replication in transformed T.thermophila cells, suggesting a more complex genetic organization than previously realized.